READING AND ENGAGEMENT: IDENTITY-MAKING IN FIGURED WORLDS - Yosep B. Margono-Slamet (Social Sciences, Humanities and Education Journal (SHE Journal), 2020)
Literary texts create imaginary or figured worlds which might engage readers. Readers engaging in imaginary or figured worlds may develop new identities. Even though readers engage in the literary texts directly, they also have indirect relationship with authors in this process. This paper draws on some influential theories such as reader response, figured worlds, and identity theories. The interaction between reader and text is dialogic; the meaning of a text depends on the transaction between readers and the text they read. On the readers’ part, they always bring their history-in-person. This influences the meaning of the text. In the end, the act of reading is an act of identity making or remaking in figured worlds. Readers shape and reshape their identity in both real and imaginary worlds